Those in peril - Smith, Wilbur A. (Thomas Dunne Books-St. Martin's Press, 2011)
An adventure set in the violent world of modern piracy and terrorism follows the kidnapping of an oil heiress's daughter for a multi-billion-dollar ransom and the efforts of Cross Bow Security head Hector Cross to secure her release.